2020
DOI: 10.5530/pj.2020.12.59
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Effect of Lampeni (Ardisia humilis Vahl.) Planting Condition toward the Alpha-glucosidase Inhibition Activity in vitro

Abstract: Background: The quality of a medicinal plant is influenced by agronomic conditions and harvesting time. Objective: This study aimed to evaluate the effect of planting method (openair (OA) and shedding house (SH)) and harvesting time (2, 4, 6 months) of Lampeni (Ardisia humilis Vahl.) toward the inhibitory activity of alpha-glucosidase. Methods: The Lampeni seedling were placed under controlled light conditions (SH) and on direct sun exposure (OA). Harvesting of the leaves was carried out at the age of 2, 4, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Alpha-glucosidase catalyzes starch and disaccharides to glucose. By inhibiting α-glucosidase, the digestion of carbohydrates slows down, which helps prevent hyperglycemia (Ningsih et al 2020). The attention of scientists has turned to the prospection and evaluation of antioxidant agents for the prevention and treatment of several diseases such as diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alpha-glucosidase catalyzes starch and disaccharides to glucose. By inhibiting α-glucosidase, the digestion of carbohydrates slows down, which helps prevent hyperglycemia (Ningsih et al 2020). The attention of scientists has turned to the prospection and evaluation of antioxidant agents for the prevention and treatment of several diseases such as diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have been working on a new practical design of α-glucosidase inhibitors from plant resources (Zahratunnisa et al 2017;Dewijanti et al 2020;Ramadhan et al 2022) that can be used as a therapeutic agent for metabolic suppression disorders such as diabetes mellitus (Halim et al 2021;Liu et al 2021). Alpha-glucosidase catalyzes starch and disaccharides to glucose (Ningsih et al 2020;Rahman et al 2021). By inhibiting α-glucosidase, the digestion of carbohydrates slows down, which helps prevent hyperglycemia (El-Shafey et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Ardisia elliptica leaves contain phytochemical compounds such as α-amyrin, β-amyrin, bauerenol, rapanone, 5-(Z-heptadec-4'-enyl) resorcinol, and 5pentadecylresorcinol [3]. Another research showed that α-amyrin and β-amyrin have activity as antihyperglicemia [9]. These compounds prevent steatosis and insulin resistance in high-fat diet-induced mouse model via the AMPK-mTORC1-SREBP1 signaling mechanism [10].…”
Section: Introductionmentioning
confidence: 99%